HUBUNGAN PENGETAHUAN PASIEN DAN DUKUNGAN KELUARGA TERHADAP KEMAMPUAN MANAJEMEN HIPOGLIKEMIA PADA PASIEN DIABETES MELLITUS TIPE II DI WILAYAH KERJA PUSKESMAS TENAYAN RAYA - Riamah Riamah; Petrus Carlos M (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Knowledge about hypoglycemia prevention, as well as family support, is an important step for self-care in people with diabetes mellitus as an effort to achieve good metabolic control. This study aims to examine the relationship between knowledge and family support with hypoglycemia management ability in type II diabetes mellitus patients in the working area of Tenayan Raya Health Center. This Research was conducted in the working area of the Tenayan Raya Community Health Center with a total population of 1923 peoples.This research uses a cross-sectional design with a sample of 95 people. The sampling technique used was purposive sampling, and data collection was conducted using a questionnaire. Statistical analysis using the Chi-square test resulted in a p-value of 0.000 (p-value 0.05) for knowledge regarding hypoglycemia management and family support regarding hypoglycemia management. Therefore, it can be concluded that there is a relationship between knowledge and the ability to manage hypoglycemia in type II diabetes mellitus patients in the working area of Tenayan Raya Health Center, and there is also a relationship between family support and the ability to manage hypoglycemia in type II diabetes mellitus patients in the working area of Tenayan Raya Health Center. The suggestion from this study is that families of type II diabetes mellitus patients are expected to provide comprehensive support by involving all domains of support needed in nursing practice. Keywords: Knowledge, Support, Family, Hypoglycemia, Diabetes Mellitus